Knowledge, attitudes, and practices regarding nutritional management in patients with chronic obstructive pulmonary disease: a cross-sectional study in rural China - Zhang, Xu; Xu, Yueqin; Duan, Yongdi; Yi, Hua; Luo, Wei (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to evaluate the knowledge, attitudes, and practices (KAP) of patients with chronic obstructive pulmonary disease (COPD) concerning nutritional management.MethodsA cross-sectional study was conducted between June and August 2024, involving COPD patients from six hospitals in Jingzhou. Demographic information and KAP scores were collected and analyzed using a self-developed questionnaire.ResultsA total of 411 valid cases were collected, with a valid response rate of 86.16%. Of the participants, 319 (77.62%) were male, 115 (27.98%) had been diagnosed with COPD for more than 10 years, and 316 (76.89%) had received education on nutritional management. The average scores for knowledge, attitudes, and practices were 7.19±5.13 (range: 0–18), 24.81±4.43 (range: 8–40), and 19.51±5.68 (range: 7–35), respectively. Correlation analysis indicated significant positive relationships between knowledge and attitudes (r = 0.629, P < 0.001), knowledge and practices (r = 0.539, P < 0.001), and attitudes and practices (r = 0.501, P < 0.001). Structural equation modeling revealed that knowledge directly influenced attitudes (β = 0.764, P < 0.001) and practices (β = 0.521, P < 0.001), while attitudes also directly impacted practices (β = 0.409, P < 0.001).ConclusionPatients with COPD demonstrated inadequate knowledge, negative attitudes, and inactive practices regarding nutritional management, highlighting a significant gap in effective dietary education. To enhance clinical outcomes, healthcare providers should implement targeted educational programs that emphasize the importance of nutritional management for COPD patients.